2001
DOI: 10.1002/1522-726x(200102)52:2<203::aid-ccd1048>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Device closure of fenestrated atrial septal defects: Use of a single Amplatz atrial septal occluder after balloon atrial septostomy to create a single defect

Abstract: Successful transcatheter device closure of secundum atrial septal defect has achieved worldwide acceptance with the clinical use of the Amplatz atrial septal occluder. However, device closure of multiple fenestrated secundum atrial septal defects remains a challenge for the interventionist and in some cases may be only effectively closed surgically. This case report of multiple fenestrated atrial septal defects represents a further expansion of technologic efforts to improve the results and simplify the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…When multiple ASDs cannot be closed with one large device or two to three smaller devices, performing an atrial balloon septostomy followed by device closure of the single iatrogenic ASD has been proposed [10]. While it has been successfully accomplished previously, this method carries the risk of creating an unpredictable, irregular, large hole.…”
Section: Discussionmentioning
confidence: 99%
“…When multiple ASDs cannot be closed with one large device or two to three smaller devices, performing an atrial balloon septostomy followed by device closure of the single iatrogenic ASD has been proposed [10]. While it has been successfully accomplished previously, this method carries the risk of creating an unpredictable, irregular, large hole.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, using multiple devices to close them separately also seems to be impossible due to the potential interference between them, although some special devices (Cribriform or PFO Amplazter) have been applied in order to avoid the device interference [8,13]. The method of using balloon atrial septostomy to allow implantation of single device was also reported [14]. The evidence is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…achieved a success rate of complete closure of both ASD in 61% of the 39 patients in whom this was attempted 6 . Alternatively, consolidation of multiple defects in a fenestrated fossa ovalis into a single large defect by simple balloon atrial septostomy followed by implantation of a single large device has been reported to effectively close all the defects 7 . When the defects are widely separated, more than one device is required.…”
Section: Discussionmentioning
confidence: 99%